PENGARUH BIMBINGAN KELOMPOK TERHADAP KEMAMPUAN PENYELESAIAN KONFLIK SISWA KELAS X SOSIAL SMA NEGERI 12 PEKANBARU TAHUN AJARAN 2013/2014 - Roma, Sendja Yandika; Arlizon, Raja; Yakub, Elny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : this research puppose to discover before and after a given group guidance, know the difference and how big an influence on students ability to resolve conlicts on aspect of collaboration, compromise, accommodate, dominates of class Social SMA N 12 Pekanbaru academic year 2013/2014. This research methodology is Quasi Eksperiment, then use the experimental design is One-Group Pretest-Posttest Design. Data collection tool used was a questionnaire. Where samples were 30 people with a random sampling technique. The description of students ability of conlict resolution before given group guidance on aspect collaboration and compromise in medium category, while acommodate and dominate in high category. After a given group guidance on aspect collaboration, compromise, and accommodate are in the high category, and dominate are in the medium category. Based on the analysis of data by using the ttest and ttable on aspect of collaboration (9,8>2,021), compromise (8,6>2,021) accommodate (3,8>2,021), dominate (9,5>2,021). Group guidance services to contribute to aspects of collaboration by 42%, compromise by 68%, accommodate by 12% and dominate 53% to the improvement of students ability to resolve conflicts of class X Social SMA N 12 Pekanbaru accademic year 2013/2014.Kata Kunci : Group Guidance, Ability of Conflict Resolution